2020
DOI: 10.1097/cad.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Intratumorally CpG immunotherapy with carbon nanotubes inhibits local tumor growth and liver metastasis by suppressing the epithelial–mesenchymal transition of colon cancer cells

Abstract: Colon cancer liver metastasis accounts for the major cause of death of colon cancer patients. Previous study reported a carbon nanotubes (CNT)-conjugated CpG complex (CNT-CpG), which displayed a significant antitumor effect in gliomas. However, whether CNT-CpG could limit colon tumor growth and suppress the colon cancer liver metastasis has not been evaluated. In this study, we report CNT enhances CpG uptake in mouse colon cancer cells. Results demonstrated only CpG with CNT conjugation showed significant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Additionally, there was a substantial decrease in the expression of EMT-related markers such as vimentin, Snail, and fibronectin 51 . In another study, epithelial cell marker E-cadherin expression increased in vivo in xenograft mice tumours, while vimentin was downregulated following CNT-CpG treatment (Figure 6 ) 52 .…”
Section: Nanomaterials As Nanovectorsmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, there was a substantial decrease in the expression of EMT-related markers such as vimentin, Snail, and fibronectin 51 . In another study, epithelial cell marker E-cadherin expression increased in vivo in xenograft mice tumours, while vimentin was downregulated following CNT-CpG treatment (Figure 6 ) 52 .…”
Section: Nanomaterials As Nanovectorsmentioning
confidence: 89%
“…(b) Treated cells were stained with DAPI and an anti-SMAD2/3 antibody. (c and d) Messenger RNA (mRNA) and protein expression of EMT marker genes were detected by real-time polymerase chain reaction and western blot, respectively 52 . Reproduced with permission.…”
Section: Figurementioning
confidence: 99%
“…This system could inhibit tumor growth [ 91 ]. Jin et al found that CNT-coupled CpG complex, in addition to showing significant anti-tumor effects in glioma, could also effectively treat local colon tumors and liver metastases, thus showing promise in related target therapy [ 173 ]. In addition to anti-tumor effects, CNTs can be used to evaluate the efficacy of tumor immunotherapies.…”
Section: Biomaterials Used In Tumor Immunotherapymentioning
confidence: 99%
“…Several studies reported the effectiveness of CNTs in cancer diagnosis and therapy, and CpG-conjugated CNTs to increase CpG uptake in mouse colon cancer cells and activate nuclear transcription factor kappa β signaling. The conjugated CpG-CNT successfully attenuated the local xenograft tumor growth and liver metastasis [54]. In contrast to their non-functional counterparts, single-walled CNT/II-NCC fluorescein-functionalized composites displayed intrinsic activity on cancer cell lines (Colon cancer cell lines-Caco-2).…”
Section: Carbon Nanotubesmentioning
confidence: 99%